The Effect Of Enviromental Cost And Enviromental Perfomance On Firm Value Moderated By Financial Perfomance - Dyah Aruning Puspita; Monica Ayu Jowana (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
Environmental concerns are now a primary focus for companies, driven by the negative impacts their operations often have on surrounding communities. Using financial performance as a moderating variable, this study examines how environmental costs and performance affect corporate value. A quantitative technique was used to study mining businesses listed on the Indonesia Stock Exchange between 2021 and 2023. SmartPLS was used to examine secondary data from these companies' annual reports. The findings show that environmental performance has a positive impact on business value, but environmental costs have no influence. Additionally, it was discovered that while financial success did not moderate the association between environmental performance and firm value, it did moderate the relationship between environmental expenses and firm value. According to these results, businesses that perform well financially are better equipped to control environmental expenses without sacrificing profitability